Vaccination against bovine mycobacterial diseases and characterization of bovine y5 T cells - Vesosky, Bridget J., author (Colorado State University. Libraries, 2001)
Mycobacterium bovis and Mycobacterium avium subspecies paratuberculosis are the causative agents of bovine tuberculosis and Johne's disease, respectively, both of which continue to seriously impact the agriculture industry. The development of novel vaccines for bovine mycobacterial diseases would likely reduce the incidence of bovine tuberculosis and Johne's disease. The M. bovis BCG vaccine has been variably efficacious against experimental M. bovis challenge, but due to interference with diagnostic tests for bovine tuberculosis it has not been used in the field. As with bovine tuberculosis, there are currently no widely used vaccines for Johne's disease. Subunit vaccines containing the proteins found in the culture media of growing mycobacteria, along with various adjuvants and cytokines, have been shown to be protective in small animal models of both human and bovine tuberculosis. Chapters 2 and 3 describe the development and testing of subunit vaccines for both bovine tuberculosis and Johne's disease in cattle, the natural host. The subunit vaccine for bovine tuberculosis consisted of culture filtrate proteins (CFP) from several virulent strains of M. bovis, along with recombinant interleukin 2 (IL- 2) and monophosphoryl lipid A (MPL). Animals were vaccinated subcutaneously three times and challenged intratracheally with a virulent strain of M. bovis. Immunological assessments were made throughout the course of the experiment and the protective efficacy of the vaccine was assessed 17 weeks following challenge at necropsy. Unlike the BCG vaccine, the CFP vaccine did not interfere with the tuberculin skin test but it failed to induce strong post-vaccination cellular immune responses and induced strong post vaccination and post challenge humoral responses. In addition, the CFP vaccine significantly reduced the severity of lung lesions found in the cattle. However, the CFP vaccine significantly increased the extrathoracic spread of M. bovis, likely an effect of the significant TH2 response that developed. Thus, although the performance of the CFP vaccine for bovine tuberculosis did not justify its use as a prophylactic vaccine, valuable information regarding the bovine immune response to CFP vaccines was obtained. Similar to the subunit vaccine for bovine tuberculosis, the subunit vaccine for Johne's disease was composed of CFP from a clinical isolate of M. a. paratuberculosis, recombinant bovine IL-2, synthetic oligodeoxynucleotides (CpGs), and dimethyl dioctadecyl ammoniumbrotnide (DDA). Animals were vaccinated subcutaneously on two occasions and challenged orally with a clinical isolate of M. a. paratuberculosis on three consecutive days. Post-vaccination and post-challenge immunological assessments were made throughout the study. Preliminary evidence suggests that the CFP/IL-2/CpG/DDA vaccine induced significantly higher percentages of αβ and γδ T cells with activated phenotypes than the adjuvants alone. Similar to the results of the M. bovis vaccine trial however, the CFP/IL-2/CpG/DDA vaccine failed to induce significant post-vaccination cellular immune responses to M. a. paratuberculosis CFP. The protective efficacy of the vaccine and the biological relevance of the activated T cell populations will be conclusively determined at the conclusion of the study. In addition to the bovine vaccine trials, this study examined phenotypic and functional characteristics of bovine γδ T cells. γδ T cells make up as much as 75% of the circulating T cell populations in cattle. More importantly, γδ T cells have been shown to be relevant in mycobacterial infections. This study identified and characterized the expression of activation markers on two peripheral blood populations of bovine γδ T cells. Interestingly, CD62L, CD44, and CD45R were identified as useful markers of activation on both populations of γδ T cells. This study demonstrated the propensity of bovine γδ T cells to expand in response to stimulation with various mycobacterial antigens. In addition, bovine γδ T cells were identified as potent producers of IFN-γ following stimulation with a component of the mycobacterial cell wall. The immunostimulatory component of the mycobacterial cell wall was identified as mycolylarabinogalactan peptidoglycan (mAGP). Given that the bovine tuberculosis and Johne's disease subunit vaccines described in this study failed to induce significant amounts of IFN-γ following vaccination, mAGP may be a useful adjuvant component of future CFP based vaccines for bovine mycobacterial diseases.
Keywords: microbiology; zoology